2019
DOI: 10.1186/s13046-019-1463-x
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH2 negatively regulates metastasis and epithelial-Mesenchymal transition via TRAF6/AKT in nasopharyngeal carcinoma

Abstract: BackgroundClinically, distant metastasis after primary treatment remains a key problem in nasopharyngeal carcinoma (NPC). Thus, identification of the underlying mechanisms and development of novel therapeutic strategies are urgently needed. NOTCH has been shown to function as a tumor promotor that enhances angiogenesis, cancer invasion and metastasis in NPC. However, the precise roles of the four individual NOTCH receptors and their mechanisms of action are unclear.MethodsWe used Western blot analysis, immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Our previous studies also confirmed that AKT is widely involved in the regulation of biological behaviors such as proliferation, cell cycling, apoptosis and invasion in NPC cells [24,32]. In the present study, we found that AKT1, AKT2, and AKT3 expression was downregulated after knockdown of CENP-N in NPC cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our previous studies also confirmed that AKT is widely involved in the regulation of biological behaviors such as proliferation, cell cycling, apoptosis and invasion in NPC cells [24,32]. In the present study, we found that AKT1, AKT2, and AKT3 expression was downregulated after knockdown of CENP-N in NPC cells.…”
Section: Discussionsupporting
confidence: 83%
“…The procedure for the cellular protein immunoprecipitation assay was described in a previous study [32]. Cells were collected and lysed in RIPA lysis buffer (Beyotime) containing a protease inhibitor cocktail (Roche Diagnostics).…”
Section: Co-ip Assaymentioning
confidence: 99%
“…Based on our findings and other reports, the metastatic ability of NPC cells correlates with EMT [31,37,55,56]. Suppressing EMT by CLCA2 and NOTCH2 can inhibit NPC metastasis in animal models [35,57]. However, direct evidence of NPC metastasis inhibition by reversing EMT or inducing mesenchymal-to-epithelial transition is unconvincing, which is part of the much larger dilemma in cancer biology studies [58].…”
Section: Epithelial To Mesenchymal Transition In Npc Metastasissupporting
confidence: 52%
“…Considering that Notch-1 and Notch-2 receptors are typically overexpressed in solid tumors [33], while the inhibition of Notch-1 by the γ-secretase complex, oppositely, results in apoptosis [34], one can assume that this event is a starting point in the enhanced proliferative activity. However, evidence exists that overexpression of Notch-2 receptor prevents metastasis and tumor growth [35] and can induce apoptosis making it an attractive target for cancer therapy [36]. In contrast, the constitutive expression of Notch-1 and silencing of Notch-1 by siRNA result in the decrease in proliferative activity and enhance apoptosis [33,34].…”
Section: Enhanced Cell Proliferation Mediated By Notch Andmentioning
confidence: 99%